No. Kontrak : UNIMAS/05/PKB/2015 (12), Perkara : UNIMAS/T(8)/2015(9) - The Supply, Delivery, Installation, Configuring, Testing and Commissioning of Network Equipments Upgrade in Universiti Malaysia Sarawak (UNIMAS), Kota Samarahan. - Universiti Malaysia Sarawak (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Perkara : UNIMAS/T(8)/2015(9) - The Supply, Delivery, Installation, Configuring, Testing and Commissioning of Network Equipments Upgrade in Universiti Malaysia Sarawak (UNIMAS), Kota Samarahan.